Social skills of higher education students in times of a Covid-19 pandemic - De La Cruz Urrutia, Lucía Lourdes (2021)
The present work is oriented to review research related to social skills developed by university students in times of covid-19 pandemic. Understanding the management and development of social skills in the process of social interaction is relevant in the university environment to obtain an adequate professional performance. Within the framework of the results, subcategories such as strategies for the development of social skills, interpersonal relationships, collaborative work and self-esteem emerged; all of them revealing that there are, visibly, young people with social deficiencies vulnerable to depressive states or lack of self-esteem. Among the conclusions it is highlighted that, as long as an efficient social development is achieved, at the same time, the student's integral growth will be reinforced; only in this way, the deficiencies in social skills will be overcome.